Schumann Resonance for Tyros c y Alexander Nickolaenko, Masashi Hayakawa. - Nickolaenko, Alexander; Hayakawa, Masashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
Schumann resonance has been studied for more than half a century. The field became popular among researchers of the terrestrial environment using natural sources of electromagnetic radiation$1 (Blightning strokes, primarily$1 (Band now many Schumann observatories have been established around the world. A huge number of publications can be found in the literature, the most recent collection of which was presented in a special Schumann resonance section of the journal Radio Science in 2007. The massive publications, however, impede finding information about how to organize measurements and start observations of global electromagnetic resonance. Relevant information is scattered throughout many publications, which are not always available. The goal of this book is to collect all necessary data in a single edition in order to describe the demands of the necessary equipment and the field-site as well as the impact of industrial and natural interference, and to demonstrate typical results and obstacles often met in measurements. The authors not only provide representative results but also describe unusual radio signals in the extremely low-frequency (ELF) band and discuss signals in the adjacent frequency ranges.s
Introductory information -- Choosing a site and positioning of equipments -- Calibrating the antennas -- Spectra of continuous SR background -- Regular SR parameters -- Disturbances in SR -- Coherence of SR -- SR line splitting -- Transient events -- Inverse problem of SR -- SR and global temperature -- Signals in adjoining frequency bands -- Extraordinary ELF signals -- Supplementary material.
Keywords: Geography; Physical geography; Earth Sciences; Geophysics/Geodesy.; Atmospheric Sciences; Statistical Physics, Dynamical Systems and Complexity